Exploring Solvent Effects on the Dialysis‐Induced Self‐Assembly of Nanostructured Tetra(aniline). Issue 11 (23rd March 2018) - Lyu, Wei; Yu, Mengting; Feng, Jiangtao; Yan, Wei
Abstract: One‐pot simple dialysis process was employed to explore the self‐assembly behavior of Ph/NH2 ‐capped tetra(aniline) (TANI) in five different solely organic solvents. Multi‐morphologies of supramolecular were assembled including nanoparticles, nanocapsules, hierarchical nanoflowers and nanowires. The solvent effects on the self‐assembly behavior were studied by differential scanning calorimetry (DSC), thermogravimetric analyzer (TGA), FT‐IR and UV‐Vis spectroscopies, 1 H NMR and powder X‐ray diffraction (PXRD), as well as density functional theory (DFT) calculations. Investigations suggested that the increase of solvent polarity facilitated the formation of hydrogen bonding between solute‐solvate. Moreover, dialysis process was found to have a profound effect on forming intermolecular π‐π stacking interaction. Such results provided not only an insight into the formation mechanism and design rule of self‐assembly behavior of nanostructured oligo(aniline)s in organic solvent‐containing complex system, but also further understanding of dialysis‐induced self‐assembly system for other nanomaterials. Abstract : Different nanostructures of tetra(aniline) were self‐assembled in five solely organic solvents via a facile dialysis process. Solvent effects on the self‐assembly of these nanostructures were explored and studies results suggested that solvent effects played the significance roles in the formation of driven forces (hydrogen bonding and π‐stacking interactions) for the self‐assembly.